Komentarz do dekretu Trybunału Roty Nuncjatury Apostolskiej w Hiszpanii c. Santiago Panizo Orallo z dnia 3 marca 1998 r. rozstrzygającego prośbę o nowe wniesienie sprawy - Białobrzeski, Tomasz (Ius Matrimoniale, 2014)
Decree on 3 March 1998 the Tribunal of the Rota of the Apostolic Nunciature in Spain negatively considered recourse the dependent in order to obtain a new presentation of the case concerning the judgment on nullity of marriage. The case was lead in the Church Court in Barcelona and next in the Tribunal of the Rota of the Apostolic Nunciature in Spain. The settlements confirmed the validity of the marriage in both instance. The defendant lodged recourse to obtain a new presentation of the case. In commented decree the request was rejected. The main motive of this decision was passive attitude of women, especially in the stage of probative' process. The noteworthy is the adjudicators deliberations concerning the new and grave proofs or argument necessary to positive consideration of the recourse (compare- the Code of Canon Law, canon 1644).